The occurrence of non-steroidal anti-inflammatory drugs (NSAIDs) in Malaysian urban domestic wastewater - Mohd Hanafiah Z.; Wan Mohtar W.H.M.; Abd Manan T.S.B.; Bachi' N.A.; Abdullah N.A.; Abd Hamid H.H.; Beddu S.; Mohd Kamal N.L.; Ahmad A.; Wan Rasdi N. (Elsevier Ltd, 2023)
Catchments; Dimers; Drug products; Ecology; Extraction; Mass spectrometry; Phase separation; Risk assessment; Sewage treatment plants; Wastewater treatment; Ecological risk assessment; Emerging contaminant; Gas chromatography mass spectrometry; Gaschromatography-mass spectrometry; Non-steroidal anti-inflammatory drug; Non-steroidal anti-inflammatory drugs; Sewage treatment plant; Sewage-treatment plants; Solid phase extraction; Solid-phase extraction; Gas chromatography; diclofenac; dimer; ibuprofen; ketoprofen; microplastic; monomer; naproxen; nonsteroid antiinflammatory agent; sorbent; surface water; drug; nonsteroid antiinflammatory agent; concentration (composition); drug; extraction method; risk assessment; wastewater; wastewater treatment; Article; calibration; catchment area (hydrology); comparative study; limit of detection; limit of quantitation; Malaysia; mass fragmentography; quality control; risk assessment; sewage treatment plant; solid phase extraction; urban area; waste water management; water quality; water sampling; wastewater; water pollutant; Malaysia; Indicator indicator; Anti-Inflammatory Agents, Non-Steroidal; Diclofenac; Naproxen; Pharmaceutical Preparations; Waste Water; Water Pollutants, Chemical